Immunological Mechanisms and Therapies in Brain Injuries and Stroke - Chen, Jun.; Hu, Xiaoming; Stenzel-Poore, Mary.; Zhang, John H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Recent research has revealed the importance of immunological mechanisms and inflammation in delaying damage and/or promoting repair after an acute injury to the central nervous system.  This book provides a comprehensive and up-to-date overview of the role of immunological mechanisms and therapies for treating acute neurological injuries such as cerebral ischemia, hemorrhage, and brain and spinal cord trauma. In several sections, the contributing authors provide a review of immunological mechanisms involved in neurological injury and of various translational and clinical research aimed at harnessing those mechanisms for better patient outcomes.
Old dogmas, surprising complexities, and novel therapeutic targets -- The critical roles of immune cells in acute brain injuries -- Vascular Inflammation in Ischemic Stroke: Adhesion Receptors Controlling Leukocyte-Endothelial Interactions -- Immune Cell-Derived Free Radicals in Acute Brain Injury -- The complement cascade in acute brain injury -- Matrix Metalloproteinases as an Inflammatory Mediator in the Neurovascular Unit -- Toll-Like Receptors in Ischemic Stroke and other Acute Brain Injuries -- Ion Transporters in Microglial Function: New therapeutic targets for neuroinflammation in ischemic stroke? -- Inflammation After Acute Brain Injuries Affects the Developing Brain Differently than the Adult Brain -- Systemic Immune Responses after Experimental Stroke -- Infectious Burden and Risk of Stroke -- Inflammatory Biomarkers in Patients with Acute Brain Injuries -- In vivo Imaging of Neuroinflammation in Acute Brain Injury -- Inflammation as a therapeutic target after subarachnoid hemorrhage: advances and challenges -- Minocycline, a Tetracycline Derivative, as a Potential Protective Agent for Acute Stroke -- Tolerization to Brain and Vascular Antigens: Targeting Autoimmunity after Acute Brain Injuries and Preventing Stroke -- The Role of PPARg in Stroke -- CD36: an inflammatory mediator in acute brain injury -- Cool Down the Inflammation:  Hypothermia as a Therapeutic Strategy for Acute Brain Injuries -- Index.
Keywords: Neurosciences; Neurology .; Neurobiology; Neurosciences; Neurology; Neurobiology